Turning fibroblasts into cardiomyocytes: technological review of cardiac transdifferentiation strategies. Issue 1 (6th September 2018) - Klose, Kristin; Gossen, Manfred; Stamm, Christof
ABSTRACT: To date, no viable therapeutic options exist for the effective and sustained reversal of cardiac failure, other than heart transplantation and mechanical circulatory assist devices. Therefore, divergent strategies aiming at the de novo formation of contractile tissue, as a prerequisite for the restoration of cardiac pump function, are currently being pursued. Clinical trials involving the transplantation of somatic progenitor cells failed. The search for alternative cell‐based strategies to combat the consequences of ischemic injury has sparked widespread interest in the genetic and pharmacologic reprogramming of fibroblasts into cardiomyocytes, harnessing the abundant in vivo pool of cardiac fibroblasts. Here, we provide a comprehensive overview of in vitro and in vivo cardiac reprogramming studies identified in an extensive literature search. We systematically review and evaluate feasibility, efficiency, and reproducibility of the different technologies currently being explored. Finally, we discuss potential safety issues deduced from preclinical studies and identify obstacles that must be overcome before clinical translation.—Klose, K., Gossen, M., Stamm, C. Turning fibroblasts into cardiomyocytes: technological review of cardiac transdifferentiation strategies. FASEB J. 33, 49–70 (2019). www.fasebj.org